Effect of injection angle, density ratio, and viscosity on droplet formation in a microfluidic T-junction. Issue 4 (July 2017) - Jamalabadi, Mohammad Yaghoub Abdollahzadeh; DaqiqShirazi, Mohammadreza; Kosar, Ali; Shadloo, Mostafa Safdari
Abstract: The T-junction microchannel device makes available a sharp edge to form micro-droplets from bio-material solutions. This article investigates the effects of injection angle, flow rate ratio, density ratio, viscosity ratio, contact angle, and slip length in the process of formation of uniform droplets in microfluidic T-junctions. The governing equations were solved by the commercial software. The results show that contact angle, slip length, and injection angles near the perpendicular and parallel conditions have an increasing effect on the diameter of generated droplets, while flow rate, density and viscosity ratios, and other injection angles had a decreasing effect on the diameter. Highlights: A parameter study on droplet formation in T-junctions is performed. Perpendicular and parallel injection angles increase the diameter. Contact angle and slip length increase the diameter. Flow rate, density, and viscosity ratios decrease the diameter.